Psychogenesis of abuse: a psychoanalytic perspective - Cerna Dorregaray, Orlando Nestor (2021)
This article studies abuse from the theoretical psychonal proposal, to understand its causes and prevent it. We review Ferenczi's studies in his famous writing: "Confusion of language between adults and children." In this document it is postulated that the abuse would occur through a type of submission of the child to the aggressor. The concept of identification with the aggressor and the introjection of what is threatening or attacking is developed. All concepts that are developed in this article. Some studies of current psychoanalysts that refer to the works of Ferenczi and Freud are also reviewed. All contribute to understanding the causal factors of mistreatment or abuse. Additionally, we include reflection on the causes of various types of abuse, such as physical, emotional, sexual and gender. All with the assurance that if we understand abuse from its origin and know its causes, then we can confront it in our environment and society in general.